Seismic performance of low-rise precast concrete structure with different types of beam-column connections using nonlinear static pushover analysis - Lim, Hung Ling (Universiti Malaysia Sarawak, UNIMAS, 2013)
Due to demand of speedy building construction and well controlled quality, precast concrete structure, being an Industrialized Building System, can replace the traditional construction method. However, the research on precast concrete structure in seismic zone is still requiring improvement. Hence, in this study, the types of beam-column connections are the main focus as the critical design parameter. Three three-storey two-dimensional precast concrete skeletal frames with three different types of beam-column connection, namely rigid, semi-rigid and pinned are modeled using structural analysis software, SAP2000V15. An earthquake excitation is simulated by applying a 10kN lateral force at a roof tip using the nonlinear static Pushover Analysis (based on FEMA356). The roof displacements of these frames versus increasing base shear are monitored and the resulting pushover curves are compared. A Seismic Demand Curve on probable earthquake in Malaysia is also constructed according to the code provision ACT-40. It is found that rigid frame can withstand the highest base shear and lowest storey drifts-joint displacement. However, a few of its beams and columns are badly damaged. The semi-rigid frame produces similar result to rigid frame with slight reduction in maximum base shear. The pinned frame can only withstand very low base shear with large storey drift-joint displacement. It collapses due to ‘Soft Storey Mechanism’ where its columns at the base floor severely damaged while beams and columns above the base floor remain unaffected. When comparing capacitydemand curves of these three frames, the structural capacities of rigid frame and semi-rigid frame are able to meet seismic demand without severe damage. However, the structural capacity of pinned frame meets the seismic demand with severe damages in structural members. As a conclusion, the rigid and semi-rigid connections are suitable to be used in precast concrete skeletal structures in Malaysia.